Systematic literature review of bacterial larvicides Bacillus thuringiensis var israelensis and Bacillus (Lysinibacillus) sphaericus for malaria control in Africa. - Mataba, Gordian Rocky (International Journal of Environmental Health Research, 2026)
A systematic review of the scientific literature was conducted with the objective of finding evidence on the contribution of microbial larvicides, Bacillus thuringiensis var israelensis and Bacillus sphaericus, in clinical malaria burden in Africa. A systematic literature search was carried out using databases PubMed, Scopus, Web of Science, ProQuest, and BASE, and Google, and Google Scholar search engines. All results were screened for duplicates and assessed for eligibility. Relevant data were extracted, and a quality assessment was performed using the CONSORT 2010 checklist, funnel plot, and Egger's regression test. Results show that 54 studies satisfied the eligibility criteria, and most were small-scale field trials. Most studies reported that Bti/Bs reduced the density of larvae of primary malaria vectors by 50%–100%. However, only 14 studies reported a subsequent reduction of malaria incidences, which was 31–62%. Furthermore, only one study evaluated the outcome of including Bti in a large-scale countrywide routine malaria control program, and it was in São Tomé and Príncipe. Overall, reviewed studies revealed a serious lack of Bti/Bs large-scale studies, and Bti/Bs inclusion in routine malaria control programs in most African countries. This impedes the formulation of evidence-based public health policies and frameworks for malaria elimination on the continent.